The concept of Tong in early China - He, Fan (2018)
Tong is one of the most important concepts for early Chinese thinkers, and playing an important role in their philosophical discourse. Despite its importance, this concept has received little scholarly attention. There is not a book or dissertation on tong in either English or Chinese scholarship. This dissertation aims to fill this gap in the literature. In avoiding the usual understandings of tong as sameness or unity, this dissertation follows the Mozi’s definition to understand tong as a description of “difference to one.” Three levels of tong are investigated: personal level, social level, and cosmic level. At the personal level, the “Wu Xing” of the Guodian bamboo slips and the Xunzi provide insights on how to achieve an ideal state of tong that unifies a person’s heart-mind, body, and conduct. At the second level, there are two different interpretations regarding the tong of society, which can be identified in the “Shang Tong” of the Mozi and the “Li Yun” of the Liji. For the third level, the Laozi, the Huainanzi, and the Wenzi employ the expression, xuan-tong, to describe an ideal relation of an individual with the cosmos. In light of the three levels of tong, this dissertation provides a Ru scholar’s view of an ideal world, which associates the tong of heart-mind, body, and conduct with the tong of society. Such a view is in contrast with the Daoist emphasis of tong on the grand scale of cosmic harmony.